2010
DOI: 10.4314/bajopas.v3i1.58756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended spectrum β-lactamases (esbls) among enterobacteriaceae in murtala mohammed specialist hospital, Kano, Nigeria

Abstract: Confirmed variants of enterobacteriaceae isolated from 143 patients that attended MurtalaMohammed Specialist Hospital Kano, were screened for extended spectrum β-lactamases (ESBLs) production using Clinical Laboratory Standards Institute (CLSI) breakpoint. Suspected ESBLs producers were subjected to confirmation using Disc Replacement Method (DRM). Standard discs of augmentin {AMC 30μg (Oxoid, England)}, ceftriaxone {AUF 30μg (Oxoid, England)} and ceftazidime {RP 30μg (Oxoid, England)} were used in the screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 10 publications
6
34
6
Order By: Relevance
“…The results showed that 37 (9.25%) isolates were ESBL producers based on DDST while only 20 (5.00%) were positive using the NCCLS breakpoints (Yusha'u et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The results showed that 37 (9.25%) isolates were ESBL producers based on DDST while only 20 (5.00%) were positive using the NCCLS breakpoints (Yusha'u et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…However, they are most common in Klebsiella pneumoniae and Escherichia coli [6]. The prevalence varies worldwide even in closely related regions [7]. In Nigeria, an ESBL prevalence of 9.25% was recorded in a study conducted by Yusha'u et al, in Kano to screen for ESBLs production among isolates of Enterobacteriaceae [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence varies worldwide even in closely related regions [7]. In Nigeria, an ESBL prevalence of 9.25% was recorded in a study conducted by Yusha'u et al, in Kano to screen for ESBLs production among isolates of Enterobacteriaceae [7]. In another study conducted in a tertiary health centre in Ogun state, Nigeria to determine ESBL prevalence in Escherichia coli and Klebsiella Species; an ESBL prevalence of 2.5% for Escherichia coli and 5% for Klebsiella pneumoniae were recorded [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in a medical college hospital, Bangladesh found 41.66% ESBL in Gram-negative bacteria [11]. A number of studies in India have reported as ESBL producers were 40.85%, 51.4% and 53.84% in 2004, 2007 and in 2010, respectively [12][13][14]. However, another two studies in Iran and India documented high prevalence 96% and 97%, respectively [15,16].…”
Section: Introductionmentioning
confidence: 99%